NEUROSIS IN BUENOS AIRES MEDICINE (1878-1900): CONCEPTS, REPRESENTATIONS AND THERAPEUTIC RESPONSES - Vallejo, Mauro Sebastián (Revista de Historia Social y de las Mentalidades, 2021)
The purpose of this article is to analyze how Buenos Aires physicians described at the end of the 19th century the nervous affections that at that time were named neurosis. A first period observes, during which neurotic diseases lacked morbid autonomy. Then, around 1890, explanations according to which these ailments were a consequence of the hectic life of modern cities gained acceptance. At the same time, those ailments received a more defined pathological entity. Finally, an interpretation of why the diagnosis of neurosis was scarcely used in public clinical devices is tested, in contrast to what happened in private enterprises.